Fréchet-valued holomorphic functions on compact sets in (DFN)-spaces - Pham, Hien Bang (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish the equivalence between the weak holomorphicity and holomorphicity of Fréchet-valued functions on compact polydisks in (DFN)-spaces. Moreover, the relations between separately holomorphic functions and holomorphic functions on compact polydisks in (DFN)-spaces are also given.